Temperature and pressure dependent thermodynamic behavior of 2H-CuInO2 - Bhamu, K. C. (AIP Conference Proceedings, 2018)
Density functional theory and quasi-harmonic Debye model has been used to study the thermodynamic properties of 2H-CuInO2. At the optimized structural parameters, pressure (0 to 80 GPa) dependent variation in the various thermodynamic properties, i.e. unit cell volume (V), bulk modulus (B), specific heat (Cv), Debye temperature (ӨD), Grǘneisen parameter (γ) and thermal expansion coefficient (α) are calculated for various temperature values. The results predict that the pressure has significant effect on unit cell volume and bulk modulus while the temperature shows negligible effect on both parameters. With increasing temperature thermal expansion coefficient increase while with increasing pressure it decreases. The specific heat remains close to zero for ambient pressure and temperature values and it increases with increasing temperature. It is observed that the pressure has high impact on Debye temperature and Grǘneisen parameter instead of temperature. Debye temperature and Grǘneisen parameter both remains almost constant for the temperature range (0-300K) while Grǘneisen parameter decrease with increasing pressure at constant temperature and Debye temperature increases rapidly with increasing pressure. An increase in Debye temperature with respect to pressure shows that the thermal vibration frequency changes rapidly.